Meta-analysis of efficacy and safety of multi-glycoside of Tripterygium wilfordii in the treatment of idiopathic membranous nephropathy - YIN Song-jiang; SHENG Mei-xiao (Linchuang shenzangbing zazhi)
Objective To evaluate the efficacy and safety of the treatment of idiopathic membranous nephropathy(IMN) by multi-glycoside of Tripterygium wilfordii(GTW).Methods The Cochrane Library,PubMed,EMbase,CBM,CNKI,VIP and WanFang were searched to enroll the randomized controlled trials(RCTs),followed by Study selection,data extraction,quality assessment,and data analyses were performed according to the Cochrane standards.RevMan 5.2 was used to analyze the information about the remission and recurrence rate of proteinuria at 6 th or 12 th month following treatment,blood levels of albumin(Alb) and serum creatinine(SCr) levels,and adverse events.Results Six articles including 886 patients were retrieved and analyzed.At 6 th month after treatment,the GTW group had a higher total remission rate(TR) than the blank control group(P<0.05),and at 12 th month after treatment,both TR and compete remission rate(CR) were higher in the GTW group than the control group.At 6 th or 12 th month after treatment,no significant difference in TR or CR was observed between the GTW+CNI group and the CNI-alone group or between the GTW group and the CNI group.However,the recurrence rate was significantly lower in the treatmemt group(P<0.05).Elevation of blood Alb and stabilization of blood SCr were observed after treatment group,which were similar to those observed after control group(P>0.05).Nevertheless,liver enzymes elevation and menstrual disorders were more frequent in the GTW group.Conclusions For IMN with total proteinuria less than 4.0 g,GTW-alone worked effectively but slowly.For IMN with total proteinuria more than 3.5 g,GTW showed a similar RT and a lower recurrence rate,as compared with CNL When used in combination with GTW,the dosage of CNI can be reduced correspondingly.On the other hand,it’s worth noticing that GTW may cause liver damage.Using GTW in women of reproductive age should be considered with caution.